Sistem Informasi Pelayanan Administrasi Kantor Kecamatan Umbu Ratu Nggay Barat Berbasis Web dengan Metode Waterfall - Yosua Pati; Adelbertus Umbu Janga; Lidia Lali Momo (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to design and implement a web-based administrative service information system at the West Umbu Ratu Nggay District Office using the Waterfall method. This information system was developed to increase efficiency and effectiveness in managing administrative services, such as writing letters, archiving documents and other administrative processes which often take a long time if done manually. By applying the Waterfall method, system development is carried out in stages, starting from requirements analysis, design, implementation, testing, to maintenance. This method was chosen because of its ability to ensure that each stage of system development is carried out in a structured and detailed manner. The research results show that the information system developed is able to automate various administrative processes at the Umbu Ratu Nggay Barat District Office, making it easier for employees to carry out their duties and improving the quality of service to the community. Evaluation of this system was carried out through functional testing and user trials, which showed that the system functions well and meets the administrative needs of the sub-district office.